Effects of Dietary Antibiotic and Cinnamon Oil Supplementation on Antioxidant Enzyme Activities, Cholesterol Levels and Fatty Acid Compositions of Serum and Meat in Broiler Chickens - Ciftci, Mehmet; Simsek, Ulku G.; Yuce, Abdurrauf; Yilmaz, Okkes; Dalkilic, Bestami (Veterinarni A Farmaceuticka Univerzita Brno, 2010)
The aim of the present study was to investigate potential hypocholesterolaemic antioxidant activities of cinnamon oil and antibiotic, and their effects on fatty acid compositions of serum and meat in broilers. A total of 240 Ross-308 chicks, five days old, were divided randomly into four treatment groups composed of 60 chicks each. Experimental groups were: corn-soybean meal basal diet (Control), basal diet supplemented with 10 ppm avilamycin (antibiotic) and 500 or 1000 ppm of cinnamon oil (C500, C1000). Cinnamon oil lowered cholesterol levels of serum (P < 0.01), breast and thigh meat (P < 0.05) in cinnamon groups compared to control and antibiotic groups. Serum malondialdehyde (MDA, nmol/g protein) level was reduced significantly in C1000 group (P < 0.05). Glutathione peroxidase (GSH-Px, mu kat/g protein) and catalase (CAT, kat/l) enzyme activities were different among the groups (P < 0.001). The higher levels of GSH-Px and CAT were obtained in C1000 group, the lower levels of these indicators were obtained in the antibiotic group. Total saturated fatty acid (SFA) ratio decreased and total unsaturated fatty acid (PUFA) ratio, omega-6 fatty acids increased significantly in serum and thigh meat in cinnamon groups (P < 0.01). These results showed that cinnamon oil had hypocholesterolaemic and antioxidant characteristics, and it also improved meat quality.
Keywords: Broiler; cinnamon oil; antioxidant enzyme activities; cholesterol level; fatty acid composition